Physical Response to Pad- and Bag-Based Boxing-Specific Training Modalities. Issue 4 (April 2020) - Finlay, Mitchell J.; Greig, Matt; McCarthy, Jake; Page, Richard M.
Abstract : Abstract: Finlay, MJ, Greig, M, McCarthy, J, and Page, RM. Physical response to pad- and bag-based boxing-specific training modalities. J Strength Cond Res 34(4): 1052–1061, 2020—This study examined the differences in the physical response elicited from a contemporary Boxing-Specific Exercise Protocol (BSEP) performed using a punch bag and a pad routine. Fourteen male elite amateur boxers (age = 22 ± 2 years; height = 176.9 ± 7.3 cm; body mass = 78.8 ± 8.7 kg; and V[Combining Dot Above]O2 max = 55.94 ± 5.96 ml·kg −1 ·min −1 ) were recruited. The BSEP comprised 3 × 3-minute rounds. Average (HRave) and peak (HRpeak) heart rate, average (V[Combining Dot Above]O2 ave) and peak oxygen consumption (V[Combining Dot Above]O2 peak), blood lactate (BLa) concentrations, rating of perceived exertion (RPE), and both triaxial and uniaxial PlayerLoad metrics were recorded during each trial. The PlayerLoad metrics were recorded at both the cervical and lumbar spine. BLa increased significantly across rounds, with higher values recorded in the pad trial (pad = 2.7 ± 0.8 mmol·L −1 ; bag = 2.3 ± 0.9 mmol·L −1 ). A similar response was also identified for the HRave (pad = 160 ± 9 b·min −1 ; bag = 150 ± 16 b·min −1 ) and V[Combining Dot Above]O2 ave data (pad = 38.00 ± 0.31 ml·kg −1 ·min −1 ; bag = 34.40 ± 1.06 ml·kg −1 ·min −1 ). A significant main effect for time was also recorded for the RPE data; however, there were no significant differences between trials. Conversely, the triaxial (PLTotal ) and medial-lateral (PLML ) data were higher in the punch bag trial. There was also a main effect for time for all the PlayerLoad metrics. PLTotal, PLML, and vertical PlayerLoad were significantly higher in the lumbar region when compared with the cervical region. With implications for boxing-specific conditioning, the pad routine was more physiologically demanding, but less mechanically demanding than the bag routine.